2020
DOI: 10.1016/j.jneb.2020.04.146
|View full text |Cite
|
Sign up to set email alerts
|

P100 Exploring the Concept of Sustainability in Nutrition and Dietetics: Student, Academic and Practitioner Perspectives

Abstract: Conclusions: This population of students may benefit from educational outreach that provides them with a better understanding of how food selection can impact climate change, and how protein requirements can be met even when meat is partially or fully replaced with various plant sources. Funding: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…19,29 The lack of more granular direction is conspicuous, given the complexity of the topic, yet not entirely surprising. Burkhart et al 25,30 observed that in Australia, generally practitioners and students are far more familiar with environmental dimensions of sustainability than they are with social and economic dimensions; however, they noted low levels of familiarity with some of these environmental dimensions, including farmland protection, soil quality and impact of diminishing arable land on global food supplies. This could indicate that a more specific level of direction on all dimensions of SFS is needed.…”
Section: Discussionmentioning
confidence: 99%
“…19,29 The lack of more granular direction is conspicuous, given the complexity of the topic, yet not entirely surprising. Burkhart et al 25,30 observed that in Australia, generally practitioners and students are far more familiar with environmental dimensions of sustainability than they are with social and economic dimensions; however, they noted low levels of familiarity with some of these environmental dimensions, including farmland protection, soil quality and impact of diminishing arable land on global food supplies. This could indicate that a more specific level of direction on all dimensions of SFS is needed.…”
Section: Discussionmentioning
confidence: 99%